1972
DOI: 10.1139/v72-323
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization by Cd(3P1) Atoms. II. Gas Phase Decomposition of Cyclohexane

Abstract: The photodecomposition of cyclohexane sensitized by Cd(3Pl) atoms has been studied in the vapor phase at 355 "C. The primary decomposition gives hydrogen atoms and cyclohexyl radicals. The volatile products of the decomposition are H,, cyclohexene, propylene, ethane, ethylene, methane, propane, butadiene, and methylcyclopentane. Products other than H2 and cyclo-C6Hlo arise from unimolecular reactions of cyclohexyl radicals, the most important such process being the production of propylene and allyl radicals. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The lower yield of CdH may result from competition between exit channels 4a and 4b at the higher energies reached with the abstractive mechanism, especially with the possibility of unimolecular energy contributions from the more complex c-C6H12 molecule. 13 Indeed, Knight and co-workers12,13 observed that extrapolation of H2 yields in Cd(3Pj)-photosensitized decomposition of both cyclopentane and cyclohexane to very low conversions led to H2 quantum yields approaching 1.0. Continuing this line of argument, it is also possible to understand why no HgH is formed in the reaction of Hg(3P0,i) with alkanes, since the total energies available are much higher, and the HgH bond energy is only 8.6 kcal as compared to 15.6 kcal in the CdH bond.…”
Section: Discussionmentioning
confidence: 99%
“…The lower yield of CdH may result from competition between exit channels 4a and 4b at the higher energies reached with the abstractive mechanism, especially with the possibility of unimolecular energy contributions from the more complex c-C6H12 molecule. 13 Indeed, Knight and co-workers12,13 observed that extrapolation of H2 yields in Cd(3Pj)-photosensitized decomposition of both cyclopentane and cyclohexane to very low conversions led to H2 quantum yields approaching 1.0. Continuing this line of argument, it is also possible to understand why no HgH is formed in the reaction of Hg(3P0,i) with alkanes, since the total energies available are much higher, and the HgH bond energy is only 8.6 kcal as compared to 15.6 kcal in the CdH bond.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper (1) it was shown that the deconlposition of cyciohexane by triplet cadmium atoms at 3261 A generally exhibited the same characteristics as the analogous triplet mercury sensitized system. Very few cadmium sensitized systems have been examined, however, and it is inlportant t o establish whether this similarity extends t o other cyclic hydrocarbons, as well as t o examine the cyclopentane system in its own right.…”
Section: Introductionmentioning
confidence: 82%
“…The apparatus and procedures have been described previously (1). The cadmium-containing reservoir attached to the reaction cell was maintained at 315 "C, while the cell itself was at 355 i 2 'C in the experinlents at fixed temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Kalra and Knight used a commercially available cadmium spectral lamp and obtained an intensity of about 4 × 10 -3 t~E rain -x at 326.1 nm. 23 We have made quartz and Pyrex glass discharge lamps, in which a few pieces of cadmium metal and a few Torr of argon were sealed. These lamps were operated at 200-300°C with 1000 V AC and gave about 0.5 t~E rain-1.…”
Section: H Experimental Methodsmentioning
confidence: 99%